Cultural Heritage as a Part of Cultural Potential (in the Context of Revitalization of Ethnic Minorities) - Lenovský, Ladislav (Studia Etnologiczne i Antropologiczne, 2019)
Cultural heritage is considered to be a valuable and representative part of the culture derived from the past. Cultural potential is a set of cultural phenomena, elements and complexes used or usable for profit. It consists of five components: heritage; organizations and institutions; events and products; infrastructure; human resources. Cultural mapping is being used for its identification, where the elements of cultural potential are cultural resources. The mapping of cultural potential with an emphasis on cultural heritage is a prerequisite for the success of revitalization of the nearly extinct ethnic group of German woodcutters from the Small-Carpathian region – Huncokars.